Analysis of Delay Handling on Sriwijaya Air Airlines at Pontianak Supadio International Airport. Essay. Diploma IV Study Program Air Transport Management Yogyakarta Aerospace Technology College. - Zhucy Ruhil Utari; Awan S.SiT.Pnb.,M.M (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
The world of aviation is currently experiencing a fairly rapid development with the large number of requests for passengers to travel for vacation or business purposes. With this request, Sriwijaya Air always provides the best service, including handling delays / delays 1) To find out what obstacles are faced by Sriwijaya Air Airlines in dealing with passengers who experience flight delays (delay) at Pontianak Supadio International Airport 2) To knowing how to handle passengers who experience flight delays on Sriwijaya Air at Supadio Pontianak International Airport. 3) To find out how Sriwijaya Air is responsible for passengers who experience flight delays that occur on Sriwijaya Air Airlines at Supadio Pontianak International Airport. The research method used in this study is a qualitative method with data collection methods carried out by direct observation, interviews and documentation. Observations were made at Pontianak Supadio International Airport in September. Meanwhile, direct interviews were conducted with Sriwijaya Air airline officers at Supadio Pontianak International Airport. The results of this study indicate that 1) that Sriwijaya Air airline officers are still experiencing problems, both problems when coordinating between divisions and obstacles in dealing with passengers during delays, 2) In this case Sriwijaya Air airline follows the procedures in handling it. Prior to providing compensation to passengers, Sriwijaya Air also provided information/announcements manually or through the AOCC, served passengers with a friendly and smiling face, and provided compensation in accordance with flight delays, 3) Sriwijaya Air airline is responsible for the airline a number of compensations. the loss stipulated by the applicable laws and regulations for the loss suffered by the passenger, but it is still possible for the passenger to obtain greater compensation by proving that the airline made a deliberate mistake.